Entre projetos e realidade : a educação ambiental como eixo transversal a partir do CEPI Alcide Jubé, Goiás/GO - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
The study proposes reflections on the role of education as a means of developing critical attitudes toward urban and industrial expansion, which has occurred rapidly and progressively in recent decades, profoundly impacting human life. This process is a consequence of a development model based on the reckless consumption of natural resources and the unequal appropriation of these resources. In contrast, there has been growing concern among various sectors of society about this reality, resulting in the formation of fronts dedicated to defending environmental awareness. This movement ranges from climate conferences to the struggles of collectives and social movements, which seek to debate the causes and consequences of environmental damage. In this context, the importance of environmental education is highlighted as a tool for raising collective awareness and sensitivity to the need for change in production and consumption models. At the same time, the question is how environmental education has been implemented in the formal school environment of CEPI Professor Alcide Jubé. How have environmental education policies been structured? And how are they effectively practiced in everyday school life? To reflect on these questions, this research aims to understand Environmental Education as a cross-cutting theme in basic education. The subject of study was the Professor Alcide Jubé Full-Time Education Center (CEPI Alcide Jubé), located in the municipality of Goiás, Goiás, from 2024 to 2025. Methodologically, in addition to the study of theoretical references and documentary collection, the research was based on Participant Observation and Action Research. The information was recorded in a field notebook, organized, and used to support the development of the presented analyses. Among other aspects, the study highlights the fragility of the environmental debate in everyday school life, evidencing a disconnect between the content covered and the concrete reality of the territories experienced by students, educators, and the community in general. Finally, the experience provided by the preparation of this work highlights the need to strengthen the content and methodologies focused on Environmental Education in schools, in order to guarantee the active involvement of students and educators in understanding and tackling socio-environmental problems from their own territories.
Keywords: Questão ambiental; Ensino; Transversalidade; Problemas socioambientais; Environmental issues; Teaching; Cross-Cutting; Socio-environmental problems; CIENCIAS HUMANAS::GEOGRAFIA